(untitled) (Cadernos de Sociomuseologia, 2010)
The Dapperstreet[1] ...Anything is a lot, when you expect so little Life keeps its wonders hidden To suddenly reveal them in a divine state. I thought about all this, Soaking wet, one drizzly morning, Simply happy in the Dapperstreet. The Dapperstreet is part of a neighbourhood often referred to as “East”, situated in the eastern part of Amsterdam. It is a lively and vibrant multi-cultural part of the city. It has a daily market with food from around the world, but is also known worldwide because of the murder on Theo van Gogh, the Dutch film director who was killed there in 2001 because of his critical and provocative statements on the Islam. Thus it can be concluded that it is certainly a neighbourhood with its own problems but, as can be read in Bloem’s poem, a place to call home and long for. [1] Poem by J.C. Bloem, The Dapperstreet (Het Verlangen, 1921). Translation by Davida de Hond.